Transformasi Ekonomi Digital Pada Perempuan Kelas Menengah-Bawah Kota Pontianak - Hosaimah .; Ismail Ruslan; Luqman . (CV. ITTC INDONESIA, 2025)
The transformation of the digital economy has significantly impacted economic behavior across various societal groups, including lower-middle-class women. This study aims to explore how women in Pontianak City adapt to the growth of the digital economy and to analyze its effects on their consumption patterns and household financial management. Employing a qualitative approach with a phenomenological design, data were collected through in-depth interviews with 12 informants actively using e-commerce platforms, digital wallets, and other financial applications. The findings reveal a shift in consumption behavior towards more impulsive spending, increased use of financial technology, and challenges related to limited digital literacy. This study highlights the ambivalent nature of digital transformation: while it offers new economic opportunities for women, it also introduces financial risks that may affect family economic stability.